Dynamic non-linear distortions of a radio over fibre system semiconductor laser - Yong, Lisa (Universiti Malaysia Sarawak, UNIMAS, 2002)
Laser dynamic non-linear distortion is one of the limitations encountered in a radio signal over fibre system. Information in the form of free space radio is transported down the optical fibre by modulating the light output of the laser diode. In this research, Volterra Series is employed to model the laser diode's dynamic non-linear distortion.